2016
DOI: 10.1103/physreve.93.022405
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of migratory and division forces as a generic mechanism for stem cell patterns

Abstract: In many adult tissues, stem cells and differentiated cells are not homogeneously distributed: stem cells are arranged in periodic "niches," and differentiated cells are constantly produced and migrate out of these niches. In this article, we provide a general theoretical framework to study mixtures of dividing and actively migrating particles, which we apply to biological tissues. We show in particular that the interplay between the stresses arising from active cell migration and stem cell division give rise t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…The bending energy is also considered in each network link: Link (i, j) uniquely determines a pair of two adjacent triangular regions, whose unit normals N (1) ij and N (2) ij in the case of Fig. 3(a Here the sign of the normals is chosen so that they have positive zcomponents at the initial membrane configuration.…”
Section: Membrane Deformationmentioning
confidence: 99%
“…The bending energy is also considered in each network link: Link (i, j) uniquely determines a pair of two adjacent triangular regions, whose unit normals N (1) ij and N (2) ij in the case of Fig. 3(a Here the sign of the normals is chosen so that they have positive zcomponents at the initial membrane configuration.…”
Section: Membrane Deformationmentioning
confidence: 99%
“…Previous work also reported that compression triggers extrusion 41,42 , whereas here we found frequent extrusion in areas of high tension. Our work provides a new experimental basis to reformulate current models of how cellular forces influence epithelial self-renewal and homeostasis 31,43 .…”
mentioning
confidence: 98%
“…The constraint of incompressibility (20) is imposed by using the fluid pressure P f as a Lagrange multiplier. In a similar way, the constraint of current conservation (19) is imposed by using the electric potential U as the Lagrange multiplier, where…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…To better understand the mechanical properties of tissues, different theoretical approaches have been developed ranging from individual cell based models [8,[12][13][14] to hydrodynamic continuum descriptions [15][16][17][18][19][20][21][22][23]. Coarse grained hydrodynamic models can be used to understand the multicellular dynamics of tissues at long wavelengths.…”
Section: Introductionmentioning
confidence: 99%